New Perspectives in the Treatment of Cushing's Syndrome - Labeur, M.; Arzt, E.; Stalla, G. K.; Paez-Pereda, M. (Current Drug Targets - Immune, Endocrine & Metabolic Disorders, 2004)
Regardless of etiology, all cases of endogenous Cushing's syndrome are due to increased production of cortisol by the adrenal gland. Most are caused by adrenocorticotrophic hormone (ACTH)-secreting pituitary adenomas. Alternatively, the glucocorticoid excess may be due to adrenal neoplasia or to ectopic ACTHsecreting tumors. Cushing's syndrome is characterized by endocrine and metabolic alterations such as truncal obesity, hypertension, weakness, amenorrhea, hyperglycemia, osteoporosis and depression. Unless treated, the disease is associated with high morbidity, and ultimately, mortality. Depending on the etiology of Cushing's syndrome two different treatment modalities are possible: reduction of pituitary ACTH production or reduction of adrenocortical cortisol secretion. In the absence of efficient drug therapy, transsphenoidal resection of the pituitary adenoma is the primary treatment of choice for the reduction of ACTH secretion. In the last years there was much progress in understanding the molecular mechanisms that control the function of the hypothalamic-pituitary-adrenal axis. Thus, new insights made it possible to identify potential drug targets for the treatment of Cushing's syndrome. The present article reviews different drug targets and therapeutic options including drugs that control the central ACTH regulation, e.g. by modulating signaling pathways and transcriptional regulation of ACTH biosynthesis, corticotrophin releasing hormone (CRH) or glucocorticoid receptor antagonists, inhibitors of glucocorticoid synthesis, ketoconazole, somatostatin and dopamine analogs. Some of these substances might be useful for the treatment of Cushing's syndrome.
Keywords: cushings syndrome